Association of Anticentromere Antibodies With More Severe Exocrine Glandular Dysfunction in Sjögren's Syndrome: Analysis of the Sjögren's International Collaborative Clinical Alliance Cohort. Issue 10 (16th September 2016) - Baer, Alan N.; Medrano, Leah; McAdams‐DeMarco, Mara; Gniadek, Thomas J.
Abstract : Objective: Anticentromere antibodies (ACAs) define a subset of primary Sjögren's syndrome (SS) with a unique phenotype, including features of limited cutaneous systemic sclerosis and a lower frequency of anti‐SSA/SSB antibodies. We sought to determine whether ACAs are associated with more severe exocrine glandular dysfunction in a large cohort of primary SS subjects. Methods: We performed a cross‐sectional analysis of 1, 361 subjects with primary SS from the Sjögren's International Collaborative Clinical Alliance Registry, stratified by the presence or absence of ACAs. ACAs were assayed by immunofluorescence staining on HEp‐2 cells. Results: ACAs were present in 82 of the 1, 361 SS subjects (6%) and were associated with older age, female sex, and lower frequencies of anti‐SSA/SSB, rheumatoid factor, and hyperglobulinemia. Among ACA‐positive versus ACA‐negative subjects, there was a higher frequency of a focus score ≥2 (71% versus 53%; P  = 0.002), a higher median focus score (2.8 versus 2.5; P  = 0.0440), and greater exocrine gland dysfunction: Schirmer's test value: median 4 versus 5 mm/5 minutes; P  = 0.0003, and unstimulated whole saliva (UWS) flow rate: median 0.08 versus 0.37 ml/5 minutes; P  < 0.0001. ACA‐positive subjects had an increased risk of UWS <0.1 ml/minute (odds ratio [OR] 12.24 [95% confidence interval (95% CI) 4.91–41.02]) and Schirmer's test value <5 mm/5 minutes (OR 2.52 [95% CI 1.50–4.36]) after correcting for age, sex, anti‐SSA/SSB, and focus score. Labial gland fibrosis was not different between the 2 groups. Conclusion: In a large international registry of SS, ACA had an independent association with more severe exocrine glandular dysfunction. This dysfunction was associated with more pronounced labial salivary glandular inflammation but not fibrosis.